DEVELOPMENT OF AN EFFECTIVE FEED MANAGEMENT SYSTEM IN POULTRY FEEDING OF CHICKENS - Zulkifli; M Azizi (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to address the persistent challenges in poultry farming feed management, particularly the inefficiency caused by reliance on manual feeding methods that often result in overfeeding or underfeeding. Method: A library research approach was employed to explore, analyze, and synthesize scientific literature relevant to feed management strategies, automation, and technological applications in poultry farming. Results: The study proposes a conceptual design for a feed management system utilizing automation and digital recording technologies to regulate the amount and timing of feed delivery with greater precision. This system has the potential to reduce feed waste by up to 20% and improve overall operational efficiency. Furthermore, the proposed development strategy leverages sensor data and real-time feed consumption monitoring to enhance productivity. The effectiveness of the system is determined by three interrelated factors: technology quality, farmers’ managerial capabilities, and environmental conditions within poultry houses. Novelty: The study offers an integrative framework combining technological innovation, data-driven decision-making, and environmental management—presenting a novel, cost-efficient solution suitable for small- to medium-scale poultry farms seeking sustainable productivity improvements.